A transforming ras gene can provide an essential function ordinarily supplied by an endogenous ras gene. - Papageorge, A G (1986)
Microinjection of monoclonal antibody Y13-259, which reacts with all known mammalian and yeast ras-encoded proteins, has previously been shown to prevent NIH 3T3 cells from entering the S phase (L. S. Mulcahy, M. R. Smith, and D. W. Stacey, Nature [London] 313:241-243, 1985). We have now found several transformation-competent mutant v-rasH genes whose protein products in transformed NIH 3T3 cells are not immunoprecipitated by this monoclonal antibody. These mutant proteins are, however, precipitated by a different anti-ras antibody. Each of these mutants lacks Met-72 of v-rasH. In contrast to the result for cells transformed by wild-type v-rasH, Y13-259 microinjection of NIH 3T3 cells transformed by these mutant ras genes did not prevent the cells from entering the S phase. These results imply that a transformation-competent ras gene can supply a normal essential function for NIH 3T3 cells. When the proteins encoded by the mutant ras genes were overproduced in Escherichia coli, several mutant proteins that lacked Met-72 failed to bind Y13-259 in a Western blot. However, a ras protein from a mutant lacking amino antibody, but a ras protein from a mutant lacking amino acids 72 to 84 did not. These results suggest that Y13-259 may bind to a higher ordered structure that has been restored in the mutant lacking amino acids 72 to 82.